Submesoscale Fronts in the Antarctic Marginal Ice Zone and Their Response to Wind Forcing. Issue 6 (17th March 2020) - Swart, Sebastiaan; du Plessis, Marcel D.; Thompson, Andrew F.; Biddle, Louise C.; Giddy, Isabelle; Linders, Torsten; Mohrmann, Martin; Nicholson, Sarah‐Anne
Abstract: Submesoscale flows in the ocean are energetic motions, O(1–10 km), that influence stratification and the distributions of properties, such as heat and carbon. They are believed to play an important role in sea‐ice‐impacted oceans by modulating air‐sea‐ice fluxes and sea‐ice extent. The intensity of these flows and their response to wind forcing are unobserved in the sea‐ice regions of the Southern Ocean. We present the first submesoscale‐resolving observations in the Antarctic marginal ice zone (MIZ) collected by surface and underwater autonomous vehicles, for >3 months in austral summer. We observe salinity‐dominated lateral density fronts occurring at sub‐kilometer scales. Surface winds are shown to modify the magnitude of the mixed‐layer density fronts, revealing strongly coupled atmosphere‐ocean processes. We posture that these wind‐front interactions occur as a continuous interplay between front slumping and vertical mixing, which leads to the dispersion of submesoscale fronts. Such processes are expected to be ubiquitous in the Southern Ocean MIZ. Plain Language Summary: Satellite radar imagery shows evidence of 1–10 km eddies and jets in the ocean adjacent to the sea‐ice edge around Antarctica. We use field observations of temperature, salinity, and wind speed from autonomous robotic platforms deployed in the sea‐ice zone for >3 months. These measurements provide estimates of the surface ocean density fronts which are controlled primarily by lateral variations in salinity. We show that, during high wind speeds, these surface fronts temporarily dissipate, indicating an atmosphere‐ocean coupling occurring at the submesoscale. The fronts strengthen again during low wind speed, which is thought to be because the stirring of the fresher surface layer by mesoscale eddies leads to the generation of the submesoscale fronts. Providing in situ observations of such features improves our understanding of the small‐scale ocean and climate processes at play, such as how heat and carbon may exchange between the atmosphere and the ocean. Key Points: Using combined surface and underwater robotic observations, we observe haline‐dominated submesoscale fronts in the Antarctic MIZ Enhanced wind speeds reduce the magnitude of lateral submesoscale fronts within the surface mixed layer Submesoscale wind‐front interactions cause a continuous interplay between front slumping and vertical mixing, arresting lateral shear